Identifying Vulnerable Brain Networks in Mouse Models of Genetic Risk Factors for Late Onset Alzheimer’s Disease - Badea, Alexandra; Wu, Wenlin; Shuff, Jordan; Wang, Michele; Anderson, Robert J.; Qi, Yi; Johnson, G. Allan; Wilson, Joan G.; Koudoro, Serge; Garyfallidis, Eleftherios; Colton, Carol A.; Dunson, David B. (Frontiers in Neuroinformatics, 2019)
The major genetic risk for late onset Alzheimer’s disease has been associated with the presence APOE4 alleles. However, the impact of different APOE alleles on the brain aging trajectory, and how they interact with the brain local environment in a sex specific manner is not entirely clear. We sought to identify vulnerable brain circuits in novel mouse models with homozygous targeted replacement of the mouse ApoE gene with either human APOE3 or APOE4 gene alleles. These genes are expressed is mice that also model the human immune response to age and disease-associated challenges by expressing the human NOS2 gene in place of mNos2. When tested for memory function these mice had impaired learning and memory as assessed with the Morris water maze and novel object recognition tests. MRI-DTI analyses revealed global and local atrophy, and areas of reduced fractional anisotropy. Using tensor network principal component analyses for structural connectomes, we inferred the pairwise connections which best separate APOE4 from APOE3 carriers. These connections involved primarily interhemispheric connections among regions of olfactory areas, the hippocampus, and the cerebellum. Our results also suggest that pairwise connections may be subdivided and clustered spatially to reveal location specific changes on a finer scale. These analyses revealed not just genotype, but also sex specific differences. Identifying vulnerable networks may provide targets for interventions and a means to stratify patients.